Nanoparticle‐Mediated Binning and Profiling of Heterogeneous Circulating Tumor Cell Subpopulations1. Issue 1 (5th November 2014) - Mohamadi, Reza M.; Besant, Justin D.; Mepham, Adam; Green, Brenda; Mahmoudian, Laili; Gibbs, Thaddeus; Ivanov, Ivaylo; Malvea, Anahita; Stojcic, Jessica; Allan, Alison L.; Lowes, Lori E.; Sargent, Edward H.; et al.
Abstract The analysis of circulating tumor cells (CTCs) is an important capability that may lead to new approaches for cancer management. CTC capture devices developed to date isolate a bulk population of CTCs and do not differentiate subpopulations that may have varying phenotypes with different levels of clinical relevance. Here, we present a new device for CTC spatial sorting and profiling that sequesters blood‐borne tumor cells with different phenotypes into discrete spatial bins. Validation data are presented showing that cancer cell lines with varying surface expression generate different binning profiles within the device. Working with patient blood samples, we obtain profiles that elucidate the heterogeneity of CTC populations present in cancer patients and also report on the status of CTCs within the epithelial‐to‐mesenchymal transition (EMT).